The structure and biological aspects of peptide antibiotic microcin J25 - Vincent, Paula Andrea (2009)
Microcin J25 (MccJ25) is a plasmid-encoded peptide of 21 L-amino acids (G1-G-A-G-H5-V-P-E-Y-F10-V-G- I-G-T15-P-I-S-F-Y20-G), excreted to the medium by an Escherichia coli strain. MccJ25 is active on Gram-negative bacteria related to the producer strain, including some pathogenic strains. The four-plasmid genes mcjABCD, are involved in MccJ25 production: mcjA encodes a 58-residue precursor, mcjB and mcjC codify two processing enzymes required for the in vivo synthesis of the mature peptide and mcjD encodes the immunity protein (McjD), a member of the super family of ABC transporters. Immunity is mediated by active efflux of the peptide, keeping its intracellular concentration below a critical level. YojI, a chromosomal protein with ATP-binding-cassette-type exporter homology, is also able to export MccJ25. The E. coli outer membrane protein, TolC, is necessary for MccJ25 secretion mediated by either McjD or YojI. The uptake of MccJ25 is dependent on the outer-membrane receptor FhuA and the four inner-membrane proteins TonB, ExbD, ExbB and SbmA. At least two mechanisms described the action of MccJ25 on the target cells: (1) inhibition of the RNA-polymerase (RNAP) activity by obstructing the secondary channel, and consequently, preventing the access of the substrates to its active sites; and (2) operating on the cell membrane, MccJ25 disrupts the electric potential inhibiting the oxygen consumption in Salmonella enterica. MccJ25 also inhibits oxygen consumption and the respiratory chain enzymes in E. coli throughout the increasing of ROS concentration. Nevertheless the exact mechanism of this phenomenon must be elucidated. The MccJ25 exhibits a prolonged antimicrobial activity in a mouse infection model, suggesting a noteworthy potential for therapeutic uses.